SMART WEDDING – PLATFORM DIGITAL PERNIKAHAN BERBASIS QR CODE DAN CIRCULAR ECONOMY - Pramudia, Komang (Universitas Lampung, 2026)
Abstract. The Indonesian wedding industry is undergoing significant transformation along with the development of digital technology and increasing awareness of tourism issues. This study aims to develop a Smart Wedding business model based on QR Code technology and a circular economy concept that focuses on efficiency, personalization, and environmental friendliness. The research method used is a descriptive qualitative approach through literature studies, field observations, and analysis using the Business Model Canvas (BMC) framework. The results show that the implementation of Smart Wedding can provide added value in the form of cost and time efficiency through QR Code-based digital invitations, reduced paper use (paperless invitations), and the use of wood waste as decoration and sustainable souvenirs. In addition, the developed business model can strengthen collaboration between vendors and expand creative economic opportunities in the digital wedding sector. Thus, Smart Wedding is not only an innovative solution in the modern wedding industry but also supports the implementation of a circular economy to realize sustainable and environmentally friendly weddings.